Teacher Reflections as Researchers in Interpreting and Evaluating Learning Practices Through and Arts Exhibition Project at SMP Negeri 2 Demak - Kinesti Alief; Sugiarto Eko (Journal of Social Work and Science Education, 2026)
This study investigates how teacher reflection, through an autoethnographic approach, contributes to understanding and evaluating learning practices implemented in an arts exhibition project in secondary school visual arts education. This qualitative autoethnographic study was conducted at SMP Negeri 2 Demak, Indonesia, involving one visual arts teacher as the researcher-participant, 32 Grade VIII students, the principal, and the vice principal for curriculum affairs. Data were collected through reflective journals, classroom observations, semi-structured interviews, and documentary evidence, and analyzed using Braun and Clarke’s thematic analysis integrated with autoethnographic interpretation. Four interconnected themes emerged: teacher reflection transformed pedagogical understanding from product-oriented to process-oriented and experiential learning; aesthetic interaction enabled collaborative meaning-making; the project encouraged a shift from product-based to authentic assessment emphasizing collaboration, creativity, and reflective thinking; and sustained reflection reconstructed teacher identity from instructional practitioner to reflective practitioner. Challenges included unequal student participation, increased assessment demands, and maintaining researcher reflexivity. This study uniquely positions teacher autoethnography as a methodological lens to capture pedagogical transformation during exhibition-based learning, an underexplored perspective in visual arts education research. Findings inform the design of authentic learning environments and reflective pedagogy in arts education. This research extends experiential learning, symbolic interactionism, and reflective practice theories by demonstrating that school-based art exhibitions function as pedagogical spaces where aesthetic engagement, authentic learning, and teacher professional development converge simultaneously.